2000
DOI: 10.1046/j.1365-2354.2000.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Greek parents’ reactions, difficulties and resources in childhood leukaemia at the time of diagnosis

Abstract: Open-ended interviews were used to examine parental psychological reactions, difficulties and resources during the period following the diagnosis of childhood leukaemia. Data were obtained from 71 randomly selected mothers and fathers of children diagnosed with leukaemia at least 3 months prior to the study. The content analysis revealed a wide diversity of parental responses including many of the defensive mechanisms described in the literature such as shock, denial, anxiety and guilt. The most difficult fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Particularly stressful consequences of accommodating the treatment needs of the ill child include changes in income and/or employment status (Enskar et al 1997;Harrington et al 2009;James et al 2002;McGrath et al 2005;Mercer and Ritchie 1997;Neil-Urban and Jones 2002;Nicholas et al 2009;Patistea et al 2000;Patterson et al 2004;Sloper 1996;Wong and Chan 2006). Indeed, a study of 151 families of children receiving active treatment reported that 46% of parents resigned from their jobs or dropped to part time to care for the ill child (James et al 2002).…”
Section: Family Strains and Day-to-day Stressorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Particularly stressful consequences of accommodating the treatment needs of the ill child include changes in income and/or employment status (Enskar et al 1997;Harrington et al 2009;James et al 2002;McGrath et al 2005;Mercer and Ritchie 1997;Neil-Urban and Jones 2002;Nicholas et al 2009;Patistea et al 2000;Patterson et al 2004;Sloper 1996;Wong and Chan 2006). Indeed, a study of 151 families of children receiving active treatment reported that 46% of parents resigned from their jobs or dropped to part time to care for the ill child (James et al 2002).…”
Section: Family Strains and Day-to-day Stressorsmentioning
confidence: 99%
“…Indeed, a study of 151 families of children receiving active treatment reported that 46% of parents resigned from their jobs or dropped to part time to care for the ill child (James et al 2002). Coupled with costs associated with cancer treatment (Mercer and Ritchie 1997), decreased income can cause financial strain (McGrath et al 2005;Mercer and Ritchie 1997;Patistea et al 2000;Patterson et al 2004), which was reported to be present in more than 50% of Greek families of children on active treatment (Patistea et al 2000) and 46% of American families of children with mixed treatment status (Sloper 1996).…”
Section: Family Strains and Day-to-day Stressorsmentioning
confidence: 99%
See 3 more Smart Citations